2019
DOI: 10.1159/000495569
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Modification for the Usage of Flexible Cystoscope in Modified Laparoscopic Pyeloplasty for Ureteropelvic Junction Obstruction with Renal Calculi: A Flexible Guiding Tube

Abstract: Objective: To present our technique of laparoscopic pyeloplasty (LP) with concomitant pyelolithotomy in ureteropelvic junction obstruction (UPJO) complicated by renal calculi and compare outcome with a group of UPJO patients undergoing modified LP without coexistent calculi. Materials and Methods: We retrospectively reviewed the charts of 51 UPJO patients undergoing modified LP from January 2013 to November 2016 at our institution. Sixteen patients were diagnosed as UPJO with coexistent ipsilateral renal calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The time to get out of bed referred to the time it takes from the end of the operation to the first time to get out of bed. The stone clearance rate was recorded and analyzed when the patient was discharged [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The time to get out of bed referred to the time it takes from the end of the operation to the first time to get out of bed. The stone clearance rate was recorded and analyzed when the patient was discharged [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…c DJ stent placement. [15]. The median stricture length was 3 cm (range 2-5 cm) according to the intraoperative measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with that in Group A, the traditional open surgery group, the stone clearance rate in Group C was significantly higher but lower than that in groups B and D. In addition, we also found that the bleeding volume, complication rate, VAS score, and LOS were significantly lower in Group C than in Groups A and B, demonstrating that the flexible cystoscope was a less invasive operation method. However, there is still a deficiency of this technique, as the use of flexible guiding tubes increase the operation time, the complexity of the procedure and the difficulty of controlling the flexible cystoscope [ 14 ]. In addition, plenty of washing fluid is needed and timely clearance of washing fluid is necessary to decrease the incidence of extravasation related perirenal infection.…”
Section: Discussionmentioning
confidence: 99%